A casein kinase 1 and PAR proteins regulate asymmetry of a PIP2 synthesis enzyme for asymmetric spindle positioning - Panbianco, Costanza; Weinkove, David; Zanin, Esther; Jones, David; Divecha, Nullin; Gotta, Monica; Ahringer, Julie (Developmental Cell, 2008)
Spindle positioning is an essential feature of asymmetric cell division. The conserved PAR proteins together with heterotrimeric G proteins control spindle positioning in animal cells, but how these are linked is not known. In C. elegans, PAR protein activity leads to asymmetric spindle placement through cortical asymmetry of G alpha regulators GPR-1/2. Here, we establish that the casein kinase 1 gamma CSNK-1 and a PIP2 synthesis enzyme (PPK-1) transduce PAR polarity to asymmetric G alpha regulation. PPK-1 is posteriorly enriched in the one-celled embryo through PAR and CSNK-1 activities. Loss of CSNK-1 1 causes uniformly high PPK-1 levels, high symmetric cortical levels of GPR-1/2 and LIN-5, and increased spindle pulling forces. In contrast, knockdown of ppk-1 leads to low GPR-1/2 levels and decreased spindle forces. Furthermore, loss of CSNK-1 leads to increased levels of PIP2. We propose that asymmetric generation of PIP2 by PPK-1 directs the posterior enrichment of GPR-1/2 and LIN-5, leading to posterior spindle displacement.